2015
DOI: 10.1166/jnn.2015.9088
|View full text |Cite
|
Sign up to set email alerts
|

Development and Quality Control of Nanohexaconazole as an Effective Fungicide and Its Biosafety Studies on Soil Nitifiers

Abstract: The study was aimed to develop a nano form of an existing fungicide for improving plant protection and reducing crop losses caused by fungal pathogens. The protocol for the preparation and estimation of nanohexaconazole was developed. Technically pure hexaconazole was converted into its nanoform using polyethyleneglycol-400 (PEG) as the surface stabilizing agent. Nanohexaconazole was characterized using Scanning Electron Microscopy (SEM) and Dynamic Light Scattering (DLS) studies. The average particle size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Indian Agriculture Research Institute (IARI), India, has developed nano-sulfur formulation against Erysiphe cichoracearum (powdery mildew of okra) [33]. In addition to this, IARI has also developed nano-hexaconazole as effective fungicide [34]. Characteristic feature of this developed formulation is biosafety aspect, and after application of nano-hexaconazole, no impact was observed on soil nitrifiers such as blue green algae and cynobacteria species.…”
Section: Nanoemulsion Formulationmentioning
confidence: 99%
“…Indian Agriculture Research Institute (IARI), India, has developed nano-sulfur formulation against Erysiphe cichoracearum (powdery mildew of okra) [33]. In addition to this, IARI has also developed nano-hexaconazole as effective fungicide [34]. Characteristic feature of this developed formulation is biosafety aspect, and after application of nano-hexaconazole, no impact was observed on soil nitrifiers such as blue green algae and cynobacteria species.…”
Section: Nanoemulsion Formulationmentioning
confidence: 99%
“…Heconazole is a pest control and a plant growth regulator. In order to reduce its adverse effects in some plants (Kumar et al 2015) have developed nanoparticles of hexaconazole using polyethyleneglycol-400 (PEG) as the surface stabilizing agent. The nanoparticles show an average size of 100 nm (SEM).…”
Section: Impact Of Nanopesticides On Non-target Soil Microorganims and Microbiomesmentioning
confidence: 99%
“…Detailed investigation of the nanopesticides includes behaviour, inhibitory properties, and the potential in suppressing the plant pathogens in field trials will help to establish a regulatory framework for their commercialisation. A new method for the preparation of nanohexaconazole was reported using polyethyleneglycol‐400 (PEG) and it was found that a nano form of hexaconazole was an efficient fungicidal agent in comparison to that of conventional hexaconazole . A sodium alginate–chitosan matrix is reported for the formulation of nanoetofenprox through entrapment having potential for effective management of Spodoptera litura .…”
Section: Nanotechnology‐based Opportunities In Crop Protectionmentioning
confidence: 99%
“…A new method for the preparation of nanohexaconazole was reported using polyethyleneglycol-400 (PEG) and it was found that a nano form of hexaconazole was an efficient fungicidal agent in comparison to that of conventional hexaconazole. 148 A sodium alginate-chitosan matrix is reported for the formulation of nanoetofenprox through entrapment having potential for effective management of Spodoptera litura. 149 In vitro, the insecticidal activity of pyridalyl nanosuspension was reported against tomato shoot and fruit borer Helicoverpa armigera, showing that insecticide load to the environment can be reduced significantly in comparison to the commercial formulations.…”
Section: Nanotechnology-based Opportunities In Crop Protectionmentioning
confidence: 99%